Reproductive Outcome of the Patients with Uterus Unicornis: Five Year Experience in a Tertiary Center - Atalay Mert, Sule; Dilbaz, Berna; Cukurova, Ece Sevin; Kose, Caner; Engin Ustun, Yaprak (Acta medica Lituanica, 2022)
Aim: The aim is to evaluate the pregnancy outcomes of patients with uterus unicornis for 5-year experience in a tertiary center. Material & Method: Twenty patients with uterus unicornis who were diagnosed with hysterosalpingography and/or 3D TVUSG between 2017 and 2021 and then confirmed with laparoscopy and simultaneous hysteroscopy were recruited for this retrospective study. The reproductive outcome and obstetric complications of the patients were followed up for two years postoperative period. Results: Overall 20 patients who fulfilled the inclusion criterion were recruited for the study. The mean age was 28.65±5.03 years. Thirteen patients (65%) had primary infertility while the remaining seven had secondary infertility with two of them having a previous ectopic pregnancy. Rudimentary communicating uterine horn was observed in 7 (35%) of the patients. The horns were excised during laparoscopy. Overall, 14 (70%) pregnancies were achieved during the 2 years follow-up period. Twelve (85.7%) patients had a live birth, (71.4% term delivery, 21.4% preterm delivery), and two had a first-trimester spontaneous abortion (15.3%). Six (50%) of 12 patients who had a live birth received tocolytics for preterm labor. Conclusion: Unicorn uterus is a rare anomaly diagnosed mostly during infertility work-out and might be related to the poor obstetric outcome, but early diagnosis is important for successful pregnancy results for preterm delivery especially in the secondary infertile group. In addition, rudimentary horn excision is recommended due to the high risk of obstetric complications.